A preliminary review of an outpatient dual diagnosis recovery group programme - Chilton, John; Parrish, Margarete; Crone, Diane (Groupwork, 2012)
The complexities of providing services suited to meet the needs of people with dual diagnoses are familiar to most professionals across mental health, substance usage and medical settings. This article discusses an ongoing recovery group therapy programme designed to address the psycho-educational and therapeutic needs associated with dual diagnoses among a diverse and complex outpatient population. As a means of addressing the multifaceted needs that characterise dual diagnoses, outpatient groups have been provided over the course of 18 months. This article presents some initial considerations resulting from observations of the therapeutic benefits of the groupwork for this challenging and often-overlooked population. Benefits of groupwork among this population and implications for good practice are discussed.